Pengaruh Biaya Produksi dan Biaya Operasional Terhadap Laba Bersih pada Perusahaan Manufaktur Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2020 - Deki, Muhammat; Chandrayanti, Teti; Bustari, Andre (Ekasakti Pareso Jurnal Akuntansi, 2024)
This study was conducted to examine the effect of production costs and operating costs on the net profit of manufacturing companies in the Pharmaceutical Sub-Sector listed on the IDX for the 2016-2020 period. The research sample consists of 7 pharmaceutical sub-sector companies listed on the IDX. Meanwhile, there are 35 total observational data determined by purposive sampling. Annual report data obtained by indo-exchange file (IDX). The technique in collecting data is through documentation. Then the technique for analyzing the data in this study is multiple linear regression using SPSS 25. The study found that production costs showed a significant effect on net income. Likewise, operating costs show a significant effect on net income. Meanwhile, it was simultaneously found that production costs and operating costs significantly affected net income.